A location-based and contextualized mobile services approach to providing information and services in the tourism industry - Carvalho, António (2019)
Todays’ market is ruled by several mobile devices applications for all types of proposes. Still, for many destinations, it lacks applications that work in an integrated way, combining cooperative mechanisms that allow the effective support the wide range of tourists need when they visit a destination. Many applications, currently available, to the tourism industry are limited in content and cultural offerings, and commercial applications only communicate with their partners and have no cultural content. This paper presents a framework of a mobile application implementation to support the tourist information needs when tourists are visiting the Portuguese city of Mirandela in which interest points are combined with commercial content. The presented model allows the tourist to have only one application that integrates the contents that he wishes/subscribes, both cultural and commercial, creating a parametrizable universal profile that can be accessed by any of the entities in the system. This approach will benefit both tourists and entities involved. This will also allow increasing the dissemination of regional products and/or services and thereby increase their market potential and consequently their sales.